A randomized controlled trial utilizing an interactive accelerometer linked to a smartphone application for enhancing physical activity and health among military employees - Pietiläinen, Emilia; Kyröläinen, Heikki; Parkkola, Kai; Luukkaala, Tiina; Vasankari, Tommi (Frontiers in Sports and Active Living, 2025)
IntroductionThe primary objectives of the present individualized randomized controlled trial were to increase physical activity (PA) and improve physical fitness.Materials and methods260 military employees around Finland participated. Two-thirds, (158), were randomized in the intervention and one-third, (101), in the control group. The intervention group used Exsed Movesense accelerometers linked to smartphones measuring PA and sleep for six months. They received feedback via a smartphone application, were encouraged to exercise during worktime for 2 hours/week, and participated in telephone counseling. The control group continued PA routines without the accelerometer or feedback. Measurements were taken at the baseline, 6-mo and 12-mo after the intervention. They included two-week RM 42-accelerometer measurements of PA, cardiometabolic biomarkers, body composition, physical fitness tests, and a questionnaire about stress and work ability for the intervention group at every point and for the control group at baseline and 12-mo. At the 6-mo, only PA was measured in the control group. Primary outcomes were changes in PA from baseline to 6-mo and 12-mo as well as changes in maximal oxygen uptake and fitness index from baseline to 12-mo. Secondary outcomes were changes in other parameters from baseline to 12-mo. The effect of the intervention on primary and secondary outcomes was analyzed using unadjusted generalised linear mixed model, accounting for a group-by-time interaction effect in all models.ResultsThere was no statistically significant group-by-time interaction regarding the measured parameters. However, amount the intervention group daily standing time (mean increase 18 min/day, 95% confidence interval [CI] 6–29 min/day) and maximal oxygen uptake (mean increase 2.15 ml/kg/min 95% CI 0.56–3.74 ml/kg/min) tended to increase during twelve months.DiscussionThe intervention did not effectively change the primary outcomes, but showed encouraging trends and revealed the potential and challenges of the intervention developed to increase PA in a military workplace.